Seismic and assessment of the high-rise RC buildings under repeated near field earthquakes with vertical component - Thinesh A/L Perumall (School of Environmental Engineering, University Malaysia Perlis, 2013)
This paper presents an extensive parametric study on the inelastic response of 18 storey reinforced concrete (RC) planar frames which are subjected to 10 single and sequential ground motions.